“Yen Ara Asaase Ni" Remix - Tuning Up the Contribution of Law in the Ghana we Desire. - Mensa-Bonsu, H.J.A.N (University of Ghana, 2023)
This second Lecture focuses on the constitutional framework in general, and issues arising thereunder, in particular. Through the lens of state-resilience, I share ideas on some constitutional issues that have featured in public discourse this past decade. As advocacy and agitations for constitutional review have increased in tempo, so has the need to address the average citizen’s appreciation of the issues at stake. For this reason, I discuss the nature of a constitution, its purpose, and its beneficiaries; and also reflect on the challenges our ethnic, religious and class diversity pose for us in our efforts to build one nation out of these many peoples. I then highlight the basic underpinnings of our Constitution, such as the principles of the rule of law and how these support state-resilience. I also discuss the citizen’s duties and note that it is the part of the bargain of democracy that is much less popular than its converse: rights. I make the point that sustaining constitutionalism and democratic governance is not just about enjoying human rights, but also about performing reciprocal duties, such as honouring one’s tax obligations. Finally, I also examine issues that are pertinent to some categories of vulnerable citizens - the aged and persons with disability - towards whom we have a duty of humanity. Such persons require more support of the State, and from the State, to enjoy their human rights – a fact which the Constitution itself recognises with appropriate provisions. Is the State doing enough in this regard, beyond passing a Disability Act? Are State agencies doing their utmost to assure their welfare? I conclude with the position that the Constitution, even in its current state, is capable of serving its purposes as it has done these thirty past years. However, Constitutions do not implement themselves and so we must do our part, first to sustain its integrity, and then support its institutions to deliver on their mandate, so that, harnessing the technologies of our time, the State can continue to play its role in providing a fulfilling life for all its citizens.
Keywords: Ghana; Law; Asaase